2019
DOI: 10.1016/j.bpj.2019.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Type IV Pilin Post-Translational Modifications Modulate Material Properties of Bacterial Colonies

Abstract: Bacterial type 4 pili (T4P) are extracellular polymers that initiate the formation of microcolonies and biofilms. T4P continuously elongate and retract. These pilus dynamics crucially affect the local order, shape, and fluidity of microcolonies. The major pilin subunit of the T4P bears multiple post-translational modifications. By interfering with different steps of the pilin glycosylation and phosphoform modification pathways, we investigated the effect of pilin post-translational modification on the shape an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 42 publications
(87 reference statements)
1
21
0
Order By: Relevance
“…Characterizing both the short-term cellular response investigated in this study and long-term viability will provide a more complete picture of how antibiotics affect colony-bound gonococci.Many bacterial species employ T4P for cell motility and aggregation[12]. In Neisseria species, T4P-T4P mediated attractive forces control the dynamics of bacteria within colonies[15][16][17]28]. Here, we show that treatment with the protein synthesis inhibitor azithromycin reduces T4P-dependent attraction and, conversely, ceftriaxone enhances the attraction.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…Characterizing both the short-term cellular response investigated in this study and long-term viability will provide a more complete picture of how antibiotics affect colony-bound gonococci.Many bacterial species employ T4P for cell motility and aggregation[12]. In Neisseria species, T4P-T4P mediated attractive forces control the dynamics of bacteria within colonies[15][16][17]28]. Here, we show that treatment with the protein synthesis inhibitor azithromycin reduces T4P-dependent attraction and, conversely, ceftriaxone enhances the attraction.…”
mentioning
confidence: 75%
“…Therefore, we wondered whether colony dynamics impacts on survivability and used bacterial strains that form less fluid colonies as revealed by characterizing the relaxation dynamics of colonies. Fluidity of gonococcal colonies can be affected by the motor activity of the T4P or by the binding strength between T4P [16, 17]. In particular, colony fluidity is strongly reduced in a strain expressing genes encoding for non-functional pilT WB T4P retraction ATPases in addition to the functional ones [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within N. gonorrhoeae colonies, cells show liquid-like order that is dependent on T4P and their retraction capability (48). Analysis using dual-laser-trap methods revealed that both motor activity and pilin posttranslational modification affect the fluidity of gonococcal colonies, with a small increase in pilus-pilus interaction strongly enhancing viscosity (48,49). This represents another striking observation expanding the role of T4P retraction beyond motility and highlighting the idea that they function in the organizational dynamics of a microcolony, with implications for resistance to various stresses.…”
mentioning
confidence: 99%